Arguments for biodiversity conservation: factors influencing their observed effectiveness in European case studies - Rob Tinch; Rob Bugter; Malgorzata Blicharska; Paula Harrison; John Haslett; Pekka Jokinen; Laurence Mathieu; Eeva Primmer (Biodiversity and Conservation, 2018)

Making a better case for biodiversity conservation: the BESAFE project - Rob Bugter; Paula Harrison; John Haslett; Rob Tinch (Biodiversity and Conservation, 2018)

Taking stock of the spectrum of arguments for biodiversity - Bruce Howard; Leon C. Braat; Rob J. F. Bugter; Esther Carmen; Rosemary S. Hails; Allan D. Watt; Juliette C. Young (Biodiversity and Conservation, 2018)

Temporal Changes in Socio-Ecological Systems and Their Impact on Ecosystem Services at Different Governance Scales: A Case Study of Heathlands - Alejandra Morán-Ordóñez; Rob Bugter; Susana Suárez-Seoane; Estanislao de Luis; Leonor Calvo (Ecosystems, 2013)

Identifying and prioritising services in European terrestrial and freshwater ecosystems - Paula A. Harrison; Marie Vandewalle; Martin T. Sykes; Pam M. Berry; Rob Bugter; Francesco de Bello; Christian K. Feld; Ulf Grandin; Richard Harrington; John R. Haslett; Rob H. G. Jongman; Gary W. Luck; et al. (Biodiversity and Conservation, 2010)

Pervasive effects of dispersal limitation on within‐ and among‐community species richness in agricultural landscapes - Frederik Hendrickx; Jean‐Pierre Maelfait; Konjev Desender; Stephanie Aviron; Debra Bailey; Tim Diekotter; Luc Lens; Jaan Liira; Oliver Schweiger; Marjan Speelmans; Viki Vandomme; Rob Bugter (Global Ecology and Biogeography, 2009)
Aim To determine whether the effect of habitat fragmentation and habitat heterogeneity on species richness at different spatial scales depends on the dispersal ability of the species assemblages and if this results in nested species assemblages. Location Agricultural landscapes distributed over seven temperate Europe countries covering a range from France to Estonia. Methods We sampled 16 local communities in each of 24 agricultural landscapes (16 km 2 ) that differ in the amount and heterogeneity of semi‐natural habitat patches. Carabid beetles were used as model organisms as dispersal ability can easily be assessed on morphological traits. The proximity and heterogeneity of semi‐natural patches within the landscape were related to average local (alpha), between local (beta) and landscape (gamma) species richness and compared among four guilds that differ in dispersal ability. Results For species assemblages with low dispersal ability, local diversity increased as the proximity of semi‐natural habitat increased, while mobile species showed an opposite trend. Beta diversity decreased equally for all dispersal classes in relation to proximity, suggesting a homogenizing effect of increased patch isolation. In contrast, habitat diversity of the semi‐natural patches affected beta diversity positively only for less mobile species, probably due to the low dispersal ability of specialist species. Species with low mobility that persisted in highly fragmented landscapes were consistently present in less fragmented ones, resulting in nested assemblages for this mobility class only. Main conclusions The incorporation of dispersal ability reveals that only local species assemblages with low dispersal ability show a decrease of richness as a result of fragmentation. This local species loss is compensated at least in part by an increase in species with high dispersal ability, which obscures the effect of fragmentation when investigated across dispersal groups. Conversely, fragmentation homogenizes the landscape fauna for all dispersal groups, which indicates the invasion of non‐crop habitats by similar good dispersers across the whole landscape. Given that recolonization of low dispersers is unlikely, depletion of these species in modern agricultural landscapes appears temporally pervasive.

Microsatellite variation and population structure of a recovering Tree frog (Hyla arborea L.) metapopulation - Paul Arens; Rob Bugter; Wendy van’t Westende; Ronald Zollinger; Jan Stronks; Claire C. Vos; Marinus J. M. Smulders (Conservation Genetics, 2006)

Microsatellite markers for the European tree frog Hyla arborea - Paul Arens; Wendy Van’t Westende; Rob Bugter; Marinus J. M. Smulders; Ben Vosman (Molecular Ecology, 2000)